Description of Aetostreon pilmatuegrossum sp. nov. from the Lower Cretaceous of Argentina (Neuquén Basin), and significance of the conservative left valve morphology in oysters of the genus Aetostreon Bayle - Rubilar Rodríguez, Alfonso Eduardo (2009)
Aetostreon pilmatuegrossum sp. nov., a large and very convex ostreid from the Pilmatué Member of the Agrio Formation (Neuquén Basin, Argentina), is described based on specimens recovered from upper Valanginian beds of the Pseudofavrella angulatiformis and Neocomites sp. ammonite subzones. This work also includes a general morphologic discussion of the well-known Lower Cretaceous oysters from Europe, Asia and Africa, most of them considered synonymous of Aetostreon latissimum (Lamarck) in the last decades. The left valves of these oysters share a set of morphological characters that seems to respond to a very distinct but conservative anatomical pattern inherited from their direct ancestor, instead of evidence for their taxonomic uniformity at the species level. Specifically, they show differences in several characters and/or their degree of development and co-occurrence in a particular growth stage, which probably have systematic value, as in the species here described. Aetostreon pilmatuegrossum sp. nov. is probable closely related to an undescribed lower Valanginian species recorded in the Chachao Formation of the Neuquén Basin, and also has affinities with an association of Barremian oysters from South Africa that seems to be its direct descendant.